The Relationship between Platelet Aggregation and CYP2C19*2, CYP2C19*3 Genotypes with Other Factors in Patients with Unstable Angina - Thi Thuy Mau, Nguyen; Thom, Vu Thi; Thao, Vu Phuong; Trung, Vu Ngoc (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2018)
The genetic polymorphism of CYP2C19 is associated with clopidogrel metabolism through the measurement of platelet aggregation in patients with unstable angina. This study was aimed to determine the frequency of CYP2C19 polymorphism and the effect of CYP2C19 genotype as well as other factors on platelet aggregation. The study was conducted on 54 patients by the cross-sectional method. The genotypes proportion of CYP2C19 *1/*1, *1/*2, *1/*3, *2/*2 and *2/*3 were 44.4%, 33.3%, 7.4%, 11.1% and 3.8%, respectively. The results with CYP2C19 phenotype were 44.4% of extensive metabolizers (EM), 40.7% of intermediate metabolizers (IM) and 14.9% of poor metabolizers (PM). For CYP2C19 *2, heterozygous genotype (GA) had higher platelet aggregation than homozygous genotype (GG) with significant difference (p=0.016). Platelet aggregation showed a significant difference between EM and (IM+PM) (p=0.027). The study results show that the prevalence of CYP2C19 *2 allele was quite high while the rate of CYP2C19 *3 allele was relatively low. Moreover, CYP2C19 *2 had a clear effect on platelet aggregation. Keywords CYP2C19 polymorphism, unstable angina, clopidogrel, platelet aggregation. References [1] E. Falk, P. K. Shah el al (1995), Coronary plaque disruption, Circulation, 92(3), 657–671. [2] H. Jneid, J.L. Anderson, R.S. Wright, C.D. Adams et al (2012), ACCF/AHA focused update of the guideline for the management of patients with unstable angina/Non-ST-elevation myocardial infarction (updating the 2007 guideline and replacing the 2011 focused update): a report of the American College of Cardiology Foundation/American Heart Association Task Force on practice guidelines, Circulation, 126(7), 875–910. [3] T.A. Nguyen, J.G. Diodatiand, C. Pharand (2005), Resistance to clopidogrel: A review of the evidence, J Am Coll Cardiol, 45, 1157–1164. [4] D.J. Angiolillo, A. Fernandez-Ortiz, E. Bernardo et al (2005), Identification of low responders to a 300-mg clopidogrel loading dose in patients undergoing coronary stenting, Thromb Res, 115(1–2), 101–108. [5] M. Haji Aghajani, F. Kobarfard et al (2013), Resistance to Clopidogrel among Iranian Patients Undergoing Angioplasty Intervention, Iran J Pharm Res, 12, 169–174. [6] D.J. Angiolillo, F. Alfonso (2007), Platelet function testing and cardiovascular out comes: steps forward in identifying the best predictive measure, Thromb Haemost, 98, 707–709. [7] S.A Scott, K. Sangkuhl, et al (2013), Clinical Pharmacogenetics Implemntation Consortium Guidelines for CYP2C19 Genotype and Clopidogrel Therapy: 2013 Update, Clin Pharmacol Ther, 94(3), 317–323. [8] I. Fricke-Galindo, C. Céspedes-Garro, F. Rodrigues-Soares (2016), Interethnic variation of CYP2C19 alleles, “predicted” phenotypes and “measured” metabolic phenotypes across world populations, Pharmacogenomics J, 16(2), 113-23. [9] J.F. Marchini et al (2017). Decreased platelet responsiveness to clopidogrel correlates with CYP2C19 and PON1 polymorphisms in atherosclerotic patients. Braz J Med Biol Res, 50(1): e56 [10] S.M. de Morais, G.R. Wilkinson et al (1994), The major genetic defect responsible for the polymorphism of S-mephenytoin metabolism in humans, J Biol Chem, 269, 15419–15422. [11] W. Tassaneeyakul, W.Mahatthanatrakul, K.Niwatananun, K.Na-Bangchang (2006). CYP2C19 genetic polymorphism in Thai, Burmese and Karen populations. Drug Metab Pharmacokinet, 21, 286–290. [12] Y.S. Yang, L.P Wong, T.C. Lee., A.M. Mustafa., Z. Mohamed and C.C. Lang (2004). Genetic polymorphism of cytochrome P450 2C19 in healthy Malaysian subjects. Br J Clin Pharmacol. [13] K.A Kim, W.K. Song, K.R. Kim (2010). Assessment of CYP2C19 genetic polymorphisms in a Korean population using a simultaneous multiplex pyrosequencing method to simultaneously detect the CYP2C19*2, CYP2C19*3, and CYP2C19*17 alleles. J Clin Pharm Ther. [14] J.H. Oestreich, L.G. Best, L.G and P.P. Dobesh (2014). Prevalence of CYP2C19 variant alleles and pharmacodynamic variability of aspirin and clopidogrel in Native Americans. Am Heart J. [15] J.A. Goldstein, Ishizaki, K. Chiba (1997). Frequencies of the defective CYP2C19 alleles responsible for the mephenytoin poor metabolizer phenotype in various Oriental, Caucasian, Saudi Arabian and American black populations. Pharmacogenetics, 7(1), 59–64. [16] K. Nakamura, F. Goto and W.A. Ray (1985). Interethnic differences in genetic polymorphism of debrisoquin and mephenytoin hydroxylation between Japanese and Caucasian populations. Clin Pharmacol Ther, 38(4), 402–408. [17] A. Maeda, H. Ando, T. Asai (2011), Differential impacts of CYP2C19 gene polymorphisms on the antiplatelet effects of clopidogrel and ticlopidine, Clin Pharmacol Ther, 89, 229–233. [18] S. Chonlaphat, T. Ramaimon, C. Montri et al (2013), CYP2C19 polymorphisms in the Thai population and the clinical response to clopidogrel in patients with atherothrombotic-risk factors, Pharmacogenomics Pers Med, 6, 85–91. [19] S. Matetzky, B. Shenkman, V. Guetta (2004), Clopidogrel resistance is associated with increased risk of recurrent atherothrombotic events in patients with acute myocardial infarction. Circulation, 109, 3171–3175. [20] Y. Arima, S. Hokimoto (2015), Comparison of the effect of CYP2C19 polymorphism on clinical outcome between acute coronary syndrome and stable angina. J Cardiol, 65,494-500 [21] K. Kaikita, T. Ono, S. Iwashita, N. Nakayama (2014), Impact of CYP2C19 polymorphism on platelet function tests and coagulation and inflammatory biomarkers in patients undergoing percutaneous coronary intervention. J Atheroclerosis Thromb, 21, 64–76. [22] J. Yang, H.D. Zhao, J. Tan, Y.L. Ding, Z.Q. Gu, J.J. Zou (2013), CYP2C19 polymorphism and [23] antiplatelet effects of clopidogrel in Chinese stroke patients. Pharm, 68, 183–186. [24] M. Zabalza, I. Subirana, J. Sala (2012), Meta-analyses of the association between cytochrome CYP2C19 loss- and gain-of-function polymorphisms and cardiovascular outcomes in patients with coronary artery disease treated with clopidogrel. Heart, 98, 100–108.